VIRTUAL REALITY TRAVERSE: A NOVEL WAY TO TEACH TRAVERSE SURVEYING - L. Lau; A. Mack; W. Yao (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
With the advancement of technology, lowered cost in hardware and widely available development tools, more and more educators across different disciplines have used virtual reality as a mean to enhance their teaching. The hit of the pandemic has also speeded up the adoption of virtual reality in education where face-to-face classes and practicals are suspended/cancelled. Virtual Reality as a tool to facilitate teaching and learning has created a new way for learners to experience the materials instead of receiving information passively through books and videos. Traverse survey is one of the main topics in surveying, it is a method used for control survey through establishing a series of points that are linked together by straight lines to form a framework. Traversing involves setting a total station and prism targets at points along the traverse line to do observations. Measurements of angles and distances are taken for the calculation of the points’ coordinates using trigonometry. This paper illustrates using freely available tools to develop a virtual reality program for doing traverse survey, the program is used in an assignment as a virtual fieldwork tool for students to learn traverse surveying at home and anywhere with a computer.